Correlation analysis between myocardial work indices and liver function classification in patients with hepatitis B cirrhosis: A study with non-invasive left ventricular pressure-strain loop - Cao, Yang; Zhang, Huihui; Li, Shuai; Li, Siliang; Sun, Shuowen; Chen, Jinwen; Ye, Ting; Zhang, Xijun; Yuan, Jianjun (Frontiers in Cardiovascular Medicine, 2023)
Background: Liver cirrhosis is closely associated with cardiac dysfunction. The aims of this study were to evaluate left ventricular systolic function in patients with hepatitis B cirrhosis by non-invasive left ventricular pressure-strain loop (LVPSL) technique, and to explore the correlation between myocardial work indices and liver function classification. Methods: According to the Child-Pugh classification, 90 patients with hepatitis B cirrhosis were further divided into three groups: Child-Pugh A group (n = 32), Child-Pugh B group (n = 31), and Child-Pugh C group (n = 27). During the same period, 30 healthy volunteers were recruited as the control (CON) group. Myocardial work parameters, which included global work index (GWI), global constructive work (GCW), global wasted work (GWW), and global work efficiency (GWE), were derived from the LVPSL and compared among the four groups. The correlation between myocardial work parameters and Child-Pugh liver function classification was evaluated, and the independent risk factors affecting left ventricular myocardial work in patients with cirrhosis were investigated by univariable and multivariable linear regression analysis. Results: GWI, GCW and GWE of Child-Pugh B and C groups were lower than those of CON group, while GWW was higher than that of CON group, and the changes were more obvious in Child-Pugh C group (P < 0.05). Correlation analysis revealed that GWI, GCW, and GWE were negatively correlated with liver function classification to various degrees (r = -0.54, -0.57, and -0.83, respectively, all P < 0.001), while GWW was positively correlated with liver function classification (r = 0.76, P < 0.001). Multivariable linear regression analysis showed that GWE was positively correlated with ALB (β = 0.17, P < 0.001), and negatively correlated with GLS (β = -0.24, P < 0.001). Conclusions: The changes in the left ventricular systolic function in patients with hepatitis B cirrhosis were identified using non-invasive LVPSL technology, and myocardial work parameters are significantly correlated with liver function classification. This technique may provide a new method for the evaluation of cardiac function in patients with cirrhosis.